2017
DOI: 10.1021/acssuschemeng.7b02091
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Radical Polymerization of Myrcene in Bulk: Mapping the Effect of Conditions on the System

Abstract: Solvent-free reversible deactivation radical polymerization of myrcene, a naturally occurring terpenoid monomer, with high regioselectivity was developed recently. Here, this green polymerization system is further improved to reach increased yields and produce polymers with high molar mass but still low dispersity and regioregular microstructure. To this end, two initiators (dibenzoyl peroxide, DBPO; azobis­(isobutyro­nitrile), AIBN) at 65, 90, and 130 °C were applied, and it was demonstrated that these varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…Due to the complexity of plant biomass, it is difficult to isolate pure macromolecules; however, biosynthesis and purification of bio-based monomers for functionalization and copolymerization are simpler and cheaper. Unlike ring-opening polymerization processes, terpenes can be polymerized using radical initiators [300].…”
Section: An Isoprenoid-derived Polymer Precursor: Natural Rubber ((C5mentioning
confidence: 99%
“…Due to the complexity of plant biomass, it is difficult to isolate pure macromolecules; however, biosynthesis and purification of bio-based monomers for functionalization and copolymerization are simpler and cheaper. Unlike ring-opening polymerization processes, terpenes can be polymerized using radical initiators [300].…”
Section: An Isoprenoid-derived Polymer Precursor: Natural Rubber ((C5mentioning
confidence: 99%
“…Myrcene is a common polymerizable monoterpene which was only recently polymerized by controlled radical polymerizations, such as reversible addition‐fragmentation chain transfer polymerization (RAFT), or nitroxide‐mediated radical polymerization (NMP) . The most significant advantage of these methods beyond their simplicity is that the produced polymers are not only controlled regarding molar mass or dispersity but also concerning regioselectivity, which was achieved previously only by non‐controlled polymerization using coordinative catalysts …”
Section: Figurementioning
confidence: 99%
“…The controlled polymerizations of Myrcene were carried out at high temperatures (up to 130 °C) mostly using azo‐ or peroxo‐initiators. Applying such high temperature does not fit into the rules of green chemistry, just like the application of several components with various reaction and dissociation rates . Also, these kinds of initiators are explosive ones, which conflicts with safety regulations besides green terms.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Early work by David presented emulsion copolymerization of styrene/methyl methacrylate and myrcene initiated by 2,2‐azobisisobutyronitrile, wherein a higher molecular weight (20 000 Da) but a lower conversion rate (5–13%) was obtained. In the last 3 years, additional works initiated by free radicals have been investigated . However, those studies revealed that free radical polymerization did not produce ideal results as they encountered issues such as longer reaction time (>15 h), uncontrollable microstructure, and unsatisfactory conversion rate (only up to 80%) .…”
Section: Introductionmentioning
confidence: 99%